Peran Abdul Haris Nasution dalam Perkembangan TNI - Weny Dea Afini; Muhammad Ricky Hardiyansyah; Abdul Azis (Polyscopia, 2024)
Abdul Haris Nasution was a high-ranking Indonesian general and politician. He served in the military during the Indonesian National Revolution and he remained in the military during the subsequent turmoil of Parliamentary democracy and Guided Democracy. This journal discusses Abdul Haris Nasution's role in the development of the Indonesian National Army (TNI). Through the historical research method, this journal describes Nasution's contribution in building and developing the TNI from 1945 to 1966. Nasution is an important figure in Indonesian military history, who played a key role in the formation and modernization of the TNI. This journal analyzes Nasution's role in strengthening the TNI's organizational structure, improving its quality and operational readiness, and fighting for the country's sovereignty. This research reveals how Nasution played a role in creating a formidable defense force for Indonesia. The purpose of this study is to understand, add insight and to know the role of A.H. Nasution in the development of the TNI, and so that this research becomes a basic reference for further research.